“Being safe means you can feel uncomfortable”: a case study of female students’ participation in a higher education, online improvisation course - MacGlone, Una M. (Frontiers in Education, 2023)
Abstract In music education contexts, improvisation is a developing area of practice and research interest. In European Higher Music Education (HME), improvisation classes often include students from different genres and courses. Accommodating students from different genre backgrounds (e.g., jazz, classical, traditional) presents pedagogical challenges in ensuring diverse students’ needs are met. In addition, there is scarce research investigating female student’s experiences of learning online. To address these issues, a recent qualitative study with four female students investigated their experiences of and views about an online free improvisation course they had taken. Students’ main disciplines were classical performance, jazz performance, education and musical theatre. Research questions investigated (1) how female students understood their learning space in an online free improvisation module and (2) what possibilities were available for creative and musical actions. A focus group and individual interviews were held after the course. Two themes were identified: the deep end and new materials, new space. Students used a common metaphor of being ‘in the deep end’ but framed this positively, either as feeling safe to experiment musically or in overcoming feelings of discomfort, perceiving an increase in self-efficacy. Findings also demonstrated that students were able to exercise agency and customise their online space by using filters; changing backgrounds and choosing when to turn their camera on and off. Appreciating female students’ perspectives and trajectories of participation can inform teachers’ priorities for creating an optimal and inclusive space for learning improvisation.